Macroevolutionary theory on macroecological patterns - Price, Peter W. (Cambridge University Press, 2003)
"In Macroevolutionary Theory on Macroecological Patterns, Peter Price establishes a completely new vision of the central themes in ecology. For the first time in book form, the study of distribution, abundance, and population dynamics in animals is cast in an evolutionary framework. The book argues that evolved characters of organisms such as morphology, behavior, and life history influence strongly their ecological relationships, including the way that populations fluctuate through time and space. The central ideas in the book are supported by data gathered from over 20 years of research, primarily into plant and herbivore interactions, concentrating on insects. The huge diversity of insect herbivores provides the immense comparative power necessary for a strong evolutionary study of ecological principles." "The book is intended as essential reading for all researchers and students of ecology, evolutionary biology, and behavior, and for entomologists working in agriculture, horticulture, and forestry."--Jacket.